(3aUd ef cJGH aj cQjI GdSeGAs - (3efUhQ Hf Ydj, CHh fUQ GHf YQGb , J fMh (B425 (3g`s
(3ChdgG (B:s
(3bO cGf ajeG cJH ChdkG Cf Gddhf GddGRhQOi jbGd Efg efbWY GdCHUGQ hCf dGTc cQi GdTcd dEfbWGY bhI GdEOQGc ai CHYGO eJSGhjI s
(3BNQgG (B:s
(3hdGSjeG Hjf ChdFc ecGf GdPi jXgQ ef gPg GdeYGfi Cbd hdCLd Pdc dGP HGdCOdI ef LgI GdWHjYI hGddg Gdehab ddUhGH , hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B110(3H (B- (3U(B114(3Cs
(3HYK GdeDda HgPG GdcJGH Edi CHj GdQjMGf eMeO Hf CMeO GdHjQhfi GdeJhai SfI (B5440 (3g` s
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs